Expression of CD markers in JAK2(V617F) positive myeloproliferative neoplasms: Prognostic significance - Shahrabi, Saeid (Oncol Rev, 2018)
Myeloproliferative neoplasms (MPNs) are clonal stem cell disorders characterized by the presence of JAK2(V617F) mutation. Thrombohemorrhagic as well as autoimmune or inflammatory phenomena are common clinical outcomes of these disorders. Recent studies have shown that abnormality in frequency and function of blood cells manifested by an alteration in CD markers’ expression patterns play a key role in these complications. So, there may be a relationship between CD markers’ expressions and prognosis of JAK2(V617F) positive MPNs. Therefore, in this review, we have focused on these abnormalities from the perspective of changing expressions of CD markers and assessment of the relationship between these changes with prognosis of JAK2(V617F) positive MPNs. It can be stated that the abnormal expression of a large number of CD markers can be used as a prognostic biomarker for clinical outcomes including thrombohememorrhagic events, as well as autoimmune and leukemic transformation in JAK2(V617F) positive MPNs. Considering the possible role of CD markers’ expressions in JAK2(V617F) MPNs prognosis, further studies are needed to confirm the relationship between the expression of CD markers with prognosis to be able to find an appropriate therapeutic approach via targeting CD markers.